Brain Iron Deficiency Changes the Stoichiometry of Adenosine Receptor Subtypes in Cortico-Striatal Terminals: Implications for Restless Legs Syndrome - Rodrigues, Matilde S. (2022)
Brain iron deficiency (BID) constitutes a primary pathophysiological mechanism in restless legs syndrome (RLS). BID in rodents has been widely used as an animal model of RLS, since it recapitulates key neurochemical changes reported in RLS patients and shows an RLS-like behavioral phenotype. Previous studies with the BID-rodent model of RLS demonstrated increased sensitivity of cortical pyramidal cells to release glutamate from their striatal nerve terminals driving striatal circuits, a correlative finding of the cortical motor hyperexcitability of RLS patients. It was also found that BID in rodents leads to changes in the adenosinergic system, a downregulation of the inhibitory adenosine A1 receptors (A1Rs) and upregulation of the excitatory adenosine A2A receptors (A2ARs). It was then hypothesized, but not proven, that the BID-induced increased sensitivity of cortico-striatal glutamatergic terminals could be induced by a change in A1R/A2AR stoichiometry in favor of A2ARs. Here, we used a newly developed FACS-based synaptometric analysis to compare the relative abundance on A1Rs and A2ARs in cortico-striatal and thalamo-striatal glutamatergic terminals (labeled with vesicular glutamate transporters VGLUT1 and VGLUT2, respectively) of control and BID rats. It could be demonstrated that BID (determined by measuring transferrin receptor density in the brain) is associated with a selective decrease in the A1R/A2AR ratio in VGLUT1 positive-striatal terminals.